Hubungan Asupan Makronutrien dengan Siklus Menstruasi pada Mahasiswa Fakultas Kedokteran Universitas Nusa Cendana Kupang - Djawa Djong, Maria Bernadetha Dua; Lidia, Kartini; Hutasoit, Regina Marvina; Lada, Christina Olly (Universitas Nusa Cendana, 2022)
Background: Macronutrient intake is needed for the availability of body energy to manage growth and development functions, including for reproductive development in women of reproductive age. Macronutrient intake which not according to the body’s needs can cause disorders of reproductive development which can be characterized by abnormal menstrual cycles. Objective: To know the correlation macronutrient intake with the menstrual cycle on medical students of Nusa Cendana University, Kupang. Methods: This research is an observational analytic research with cross sectional design. The sampling technique used was consecutive sampling with 60 sampelts who fulfilled inclusion criteria. The collection of data used menstrual cycle questionnaire, food recall 2x24 hours, standardized food ingredient models, and nutrisurvey. Bivariate analysis used Chi-square test with alternative test Fischer’s exact test. Results: There is 20% students have an abnormal menstrual cycle. The results of the bivariate analysis showed no significant correlation between carbohydrate intake (p = 0.200); protein intake (p = 0.743); and fat intake (p = 0.670) with menstrual cycle on medical students of Nusa Cendana University. Conclusion: There is no significant correlation between macronutrient intake with menstrual cycle on Medical Students of Nusa Cendana University, Kupang.